Ground state depletion microscopy as a tool for studying microglia–synapse interactions. Issue 6 (7th March 2021) - Paasila, Patrick Jarmo; Fok, Sandra Y. Y.; Flores‐Rodriguez, Neftali; Sajjan, Sujata; Svahn, Adam J.; Dennis, Claude V.; Holsinger, R. M. Damian; Kril, Jillian J.; Becker, Thomas S.; Banati, Richard B.; Sutherland, Greg T.; Graeber, Manuel B.
Abstract: Ground state depletion followed by individual molecule return microscopy (GSDIM) has been used in the past to study the nanoscale distribution of protein co‐localization in living cells. We now demonstrate the successful application of GSDIM to archival human brain tissue sections including from Alzheimer's disease cases as well as experimental tissue samples from mouse and zebrafish larvae. Presynaptic terminals and microglia and their cell processes were visualized at a resolution beyond diffraction‐limited light microscopy, allowing clearer insights into their interactions in situ . The procedure described here offers time and cost savings compared to electron microscopy and opens the spectrum of molecular imaging using antibodies and super‐resolution microscopy to the analysis of routine formalin‐fixed paraffin sections of archival human brain. The investigation of microglia–synapse interactions in dementia will be of special interest in this context.